Use of Various Types of Chitosan as Edible Coating to Maintain Physical Quality of Tomatoes (Solanum lycopersicon L.) During Storage at Two Different Temperatures - Novia Asri Nasution; M. Idris (Jurnal Biologi Tropis, 2023)
Increasing tomato production requires special handling to increase longer shelf life by applying chitosan and modifying storage temperatures. Chitosan is a chitin derivative whose function is similar to wax compounds so that it is able to inhibit metabolic activity. Storage temperature of 10°C can extend shelf life and maintain the physical quality of tomatoes. This study aims to determine the effect of chitosan administration, the effect of storage temperature, and the effect of the combination of chitosan and storage temperature on the physical quality of tomatoes. This study used a Factorial Complete Randomized Design, the first factor was tomatoes without chitosan coating (K0), and tomatoes with chitosan coating (K1) = shrimp shell, (K2) = crab shell, (K3) = fish scales using the same concentration of 6%. The second factor is storage temperature (T1) = room temperature (26-32°C) and (T2) = temperature 10°C.  The changes observed are shrinkage in weight, color, texture, aroma, taste based on organoleptic test (hedonic test). Data analysis using ANOVA at 5% level and BNJ follow-up test at 5% level. The results showed that the use of crab chitosan (K2) had an effect on weight loss (0.42%). Storage temperature of 10°C (T2) affects weight loss (5.04%). The best treatment combination for weight loss (0.07%) and color (7.40) was crab chitosan and temperature of 10°C (K2T2), while the best treatment combination for texture (7.56), aroma (7.08), and taste (7.16) was fish scales and temperature of 10°C (K3T2). In general, the best treatment is chitosan fish scales and a temperature of 10°C (K3T2).